DEVELOPING ONLINE FORMATIVE ASSESSMENT USING QUIZIZZ FOR ASSESSING READING COMPETENCY OF THE TENTH GRADE STUDENTS IN BULELENG REGENCY - Ari Puspitayani, Desak Made; Jaya Putra, I Nyoman Adi; Santosa, Made Hery (Universitas Pendidikan Ganesha, 2020)
This research and development study (R&D) aimed to: (1) develop online quiz prototype using Quizizz and (2) examine the quality of the developed online quiz. This study employed Four-D model with Define, Design, Develop, and Disseminate phases by Thiagarajan (1974). The subjects of this study were 10 Senior High School English Teachers in Buleleng regency. The data about the teachers? need were collected by administering questionnaire and analyzing the teachers? documents while the quality of the developed online quiz was validated by expert and user judges. The data of the teachers? need were analyzed descriptively. The quality of the developed online quiz in terms of content validity was analyzed by using Gregory?s formula while the practicality was analyzed by using practicality criteria. The results of the study shows that the teachers need online quiz as formative assessment instruments which consisted of of linguistic and level comprehension aspects. The prototype of online formative assessment was initiated in define phase by doing target situation analysis, learner analysis, concept analysis, task analysis, and present situation analysis. The quality of the developed online quiz was examined in develop phase. The result of the study shows that the quality of the developed online quizzes as a formative assessment in terms of content validity was very high and the practicality was excellent. The implication of this finding is that the developed online quiz as formative assessment instrument is highly recommended to be implemented in the real classroom and widely disseminated. It is not only beneficial for the teachers in teaching and learning process but also improve teachers? competence. Therefore, this formative assessment instrument is ready to be used for assessing the tenth grade students? reading competency. Keywords: formative assessment; online quiz; prototype; reading competency; teachers? competency